2022
DOI: 10.1002/ejhf.2441
|View full text |Cite
|
Sign up to set email alerts
|

A promise unfulfilled: the use of mineralocorticoid receptor antagonists in patients with heart failure and a reduced left ventricular ejection fraction

Abstract: This article refers to 'Temporal trends in initiation of mineralocorticoid receptor antagonists and risk of subsequent withdrawal in patients with heart failure: a nationwide study in Denmark from 2003-2017' by D. Zahir et al., published in this issue on pages 539-547.The steroidal mineralocorticoid receptor antagonists (MRAs) reduce mortality and hospitalizations for heart failure (HHF) in patients with heart failure and a reduced ejection fraction (HFrEF). Their incorporation into US and European guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…6 Indeed, MRAs may be more underutilized than any other evidence-based therapy for HFrEF, prompting a recent trial specifically aimed at overcoming this problem. [7][8][9] Scrutiny of prescribing patterns suggests that MRAs are still reserved for patients with more severe functional limitation (NYHA functional classes III and IV) even though the EMPHASIS-HF (Eplerenone in Mild Patients Hospitalization and Survival Study in Heart Failure trial; NCT00232180) trial showed that eplerenone reduced the risks of both death and heart failure (HF) hospitalization in patients with mild symptoms, ie, in NYHA functional class II. 1 Physicians may be reluctant to add another treatment in patients with long-standing HF who appear to be stable on their current therapy and are mistakenly thought to be at low risk.…”
mentioning
confidence: 99%
“…6 Indeed, MRAs may be more underutilized than any other evidence-based therapy for HFrEF, prompting a recent trial specifically aimed at overcoming this problem. [7][8][9] Scrutiny of prescribing patterns suggests that MRAs are still reserved for patients with more severe functional limitation (NYHA functional classes III and IV) even though the EMPHASIS-HF (Eplerenone in Mild Patients Hospitalization and Survival Study in Heart Failure trial; NCT00232180) trial showed that eplerenone reduced the risks of both death and heart failure (HF) hospitalization in patients with mild symptoms, ie, in NYHA functional class II. 1 Physicians may be reluctant to add another treatment in patients with long-standing HF who appear to be stable on their current therapy and are mistakenly thought to be at low risk.…”
mentioning
confidence: 99%
“…(5) No obstante, el hecho de que solo entre un tercio y la mitad de los pacientes con ICFEP reciban este tratamiento refleja la incertidumbre que aún persiste sobre su valor, una pregunta que se espera sea respondida por los ensayos en curso con antagonistas de los receptores de mineralocorticoides. (6) Los últimos hallazgos cruciales del presente registro son los resultados clínicos informados entre los pacientes inscritos, con una tasa anualizada del criterio de valoración compuesto de muerte por causas cardiovasculares u hospitalización por empeoramiento de la insuficiencia cardíaca del 12,8%, hospitalización por empeoramiento de la insuficiencia cardíaca del 9,8%, muerte por causas cardiovasculares del 6,6%, y muerte por cualquier causa del 8,4%. Si bien estas tasas son tan "buenas" como las observadas en ensayos recientes, lo que refleja la excelente terapia mencionada anteriormente, resaltan la necesidad de continuar desarrollando nuevos tratamientos y reducir aún más las tasas de eventos en la insuficiencia cardíaca.…”
unclassified